2013
DOI: 10.9790/2402-0243845
|View full text |Cite
|
Sign up to set email alerts
|

Lead and Cadmium assay in Serum and Semen of Infertile Men attending Andrology clinic in Assiut University Hospital (Rural versus Urban)

Abstract: Recently, environmental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…On the other hand, as it can be observed in Fig. 2, Cd concentrations measured in this study were comparable to those reported in population from Egypt (Saleh et al 2013) and Japan (Katayose et al 2004), and higher than Cd levels measured in people of USA (Pleban and Mei 1983), Singapore (Xu et al 1993), and Kuwait (Omu et al 1995), etc. In this study, high concentrations of Cd in seminal plasma of Pakistani population may be related to the extended industrial and agricultural activities.…”
Section: Cadmium (Cd)supporting
confidence: 92%
“…On the other hand, as it can be observed in Fig. 2, Cd concentrations measured in this study were comparable to those reported in population from Egypt (Saleh et al 2013) and Japan (Katayose et al 2004), and higher than Cd levels measured in people of USA (Pleban and Mei 1983), Singapore (Xu et al 1993), and Kuwait (Omu et al 1995), etc. In this study, high concentrations of Cd in seminal plasma of Pakistani population may be related to the extended industrial and agricultural activities.…”
Section: Cadmium (Cd)supporting
confidence: 92%
“…The mixture was analysed by atomic absorption spectrophotometer (GBC 933 plus), with air-acetylene flame and hollow cathode lamp (Medhat et al, 2013). Serum Mg and Zn concentrations were determined by using commercial kits with spectrophotometer (Oladipo and Temiye, 2005).…”
Section: Determination Of the Divalent Ionsmentioning
confidence: 99%
“…There were some highly significant negative correlations between normal sperm morphology (r -0.55, p<O.00l) and seminal plasma cadmium concentration, and between progressive sperm motility (r -0.66, p<0.001) and seminal plasma cadmium concentration. Overall, this study suggests that infertile men from urban areas are more at risk of exposure to hazardous environmental toxicants like cadmium and this requires special attention in management of those men attending infertility clinics and belonging to urban areas (148).…”
Section: Effect Of CD On Reproductive Hormones and Sperm Parametersmentioning
confidence: 88%
“…This study was done to compare serum and seminal plasma levels of lead and cadmium in rural versus urban infertile men from Assiut governorate in Egypt, and also to detect the correlations of these heavy metals with conventional semen parameters and sperm vitality (148). Fifty eight infertile men were included in this study.…”
Section: Effect Of CD On Reproductive Hormones and Sperm Parametersmentioning
confidence: 99%
See 1 more Smart Citation